Question de la taille des arbres dans des jardins japonais de France : rencontres et réflexions entre jardiniers français et japonais - Yoko Mizuma (Projets de Paysage)
In France today, the art of Japanese gardening still arouses a great deal of curiosity. The art of pruning is a particularly important topic since it impacts the daily work of gardeners in plant maintenance. It affects the spatial organisation of the garden and concerns landscape architects. In France, where the historical background in the development of pruning techniques as well as the climatic conditions differ from those in Japan, pruning is one of the key aspects affecting the form of Japanese gardens. The aim of this article is to present some of the characteristics of Japanese gardens in France with a focus on the pruning techniques and their contribution.